Analysis of Delivery Order Services in Increasing Sales from an Islamic Economics Perspective - Maulida Ghina Faizah; Moh. Idil Ghufron (STAI Al-Mas'udiyah, 2026)
The popularity of delivery order services in Indonesia has increased rapidly alongside the shift of consumer behavior toward digital platforms. This phenomenon is not only observed in urban areas but is also increasingly evident among micro-scale culinary businesses in rural regions, such as Mie Jebew Julid in Desa Besuk. This study aims to analyze the role of delivery order services in increasing the sales of Mie Jebew Julid and to examine these service practices from an Islamic economic perspective. The research employed a qualitative descriptive approach with a case study method. The results indicate that the delivery order service significantly contributes to sales growth. From January to September 2025, an average of 31% of total sales came from delivery orders, peaking at 40%. Service quality analysis based on SERVQUAL dimensions showed positive results, particularly in reliability and responsiveness, although limited staff during peak hours posed challenges. From an Islamic economic perspective, the service practices align with the principles of amanah (trustworthiness), shidq (honesty), ‘adl (justice), and responsibility, reflected in clear information, timely delivery, and consumer care. The integration of professional service quality and Islamic ethical values fosters consumer trust, increases purchase frequency, and supports the sustainable growth of rural micro-scale culinary businesses.